Anticipation, Tax Avoidance, and the Price Elasticity of Gasoline Demand. (21st January 2016) - Coglianese, John; Davis, Lucas W.; Kilian, Lutz; Stock, James H.
Summary: Least‐squares estimates of the response of gasoline consumption to a change in the gasoline price are biased toward zero, given the endogeneity of gasoline prices. A seemingly natural solution to this problem is to instrument for gasoline prices using gasoline taxes, but this approach tends to yield implausibly large price elasticities. We demonstrate that anticipatory behavior provides an important explanation for this result. Gasoline buyers increase purchases before tax increases and delay purchases before tax decreases, rendering the tax instrument endogenous. Including suitable leads and lags in the regression restores the validity of the IV estimator, resulting in much lower elasticity estimates. Copyright © 2016 John Wiley & Sons, Ltd.